2017
DOI: 10.7150/ijbs.22175
|View full text |Cite
|
Sign up to set email alerts
|

Azadirachtin induced apoptosis in the prothoracic gland in Bombyx mori and a pronounced Ca2+ release effect in Sf9 cells

Abstract: Azadirachtin is a bio-rational insecticide used as an antifeedant and growth disruption agent against many insect species. However, recent studies have shown that there is a potential risk of this compound harming some beneficial insects. In such cases its application does not normally lead to death, but it may result in altered developmental regulation. Therefore, it is essential to obtain toxicological data to understand the mechanism of such sub-lethal effects, especially where they relate to important bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…For TUNEL, after the testis were dissected from treated and control moths, they were collected and fixed with 4% paraformaldehyde overnight at 4 °C, washed four times with PBS for 5 min at room temperature and stored in 70% ethanol at –20 °C until use. After sectioned, the sample was detected by using a commercial kit (Apo‐Direct TUNEL assay kit, Millipore) as described previously . Then the treated samples were observed by transmission electron microscope (TEM).…”
Section: Methodsmentioning
confidence: 99%
“…For TUNEL, after the testis were dissected from treated and control moths, they were collected and fixed with 4% paraformaldehyde overnight at 4 °C, washed four times with PBS for 5 min at room temperature and stored in 70% ethanol at –20 °C until use. After sectioned, the sample was detected by using a commercial kit (Apo‐Direct TUNEL assay kit, Millipore) as described previously . Then the treated samples were observed by transmission electron microscope (TEM).…”
Section: Methodsmentioning
confidence: 99%
“…The HeLa cells were then harvested, washed with PBS and fixed with 2.5% glutaraldehyde at 4˚C for 12 h. Following washing with PBS, HeLa cells were dehydrated with ethanol and acetone, sequentially fixed with 1% osmium tetroxide (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) for 2 h at 37˚C, followed by embedding in epoxy resin for 12 h at 37˚C. Ultra-thin slices (80 nm) were then produced, stained with 1.0% uranylacetate for 5 min at room temperature and viewed on a transmission electron microscope (23,24).…”
Section: Dapi Staining and Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…Apoptosis has been reported in different insect cell lines treated with azadirachtin, including SL-1 ( S. litura ), BTI-Tn-5B1–4 ( Trichoplusia ni ) and S2 ( Drosophila melanogaster ) 26,29,30 . In addition, it has also been observed in prothoracic glands of Bombyx mori and in midgut of S. litura after treated with azadirachtin 31,32 . Our previous studies indicated that azadirachtin could activate mitochondrial and lysosomal pathways that lead to apoptosis in Sf9 cells 1,8,33 .…”
Section: Discussionmentioning
confidence: 88%